THE UNCERTAIN UNCERTAINTY OF RIVER BASINS: ACCOUNTING FOR UNCERTAINTY IN INTEGRATED WATER RESOURCES MANAGEMENT (IWRM) - Allen, Sarah (European Scientific Journal, ESJ, 2013)
Integrated Water Resources Management was officially established under the 1992 Dublin Principles. A set of standard principles was thought to be the ‘state-of-the-art’ solution to problems of ensuring good management, governance, distribution, and usage across the world. Therefore, this ‘perfect’ solution has become a leading discourse in water governance and management. However, current water related problems leave the Principles unrealistic and too idealistic for real success. Without responding to the lack of transparency and accountability, IWRM will not have the capacity to manage uncertainty in the future as global environmental changes continue. Following a case study from the Mekong River Basin, this paper will discuss how IWRM does not accurately account for issues of uncertainty in the water system and provides a plausible solution to this problem.